Cytoarchitecture and probability maps of the human medial orbitofrontal cortex. (February 2016) - Henssen, Anton; Zilles, Karl; Palomero-Gallagher, Nicola; Schleicher, Axel; Mohlberg, Hartmut; Gerboga, Fatma; Eickhoff, Simon B.; Bludau, Sebastian; Amunts, Katrin
Abstract: Previous architectonical studies of human orbitofrontal cortex (OFC) provided divergent maps regarding number, location, and extent of areas. To solve this controversy, an observer-independent cytoarchitectonical mapping of medial OFC (mOFC) was performed. Borders of cortical areas were detected in histological sections of ten human post-mortem brains using a quantitative, statistically testable method, and their stereotaxic localization and intersubject variability were determined. Three areas were identified: granular Fo1 mainly on the rostral Gyrus rectus and medial of the olfactory sulcus; granular to dysgranular Fo2, mainly on the posterior part of the ventromedial Gyrus rectus and the medial and lateral banks of the olfactory sulcus; granular Fo3 between the olfactory and medial or intermediate orbital sulci. Fo3 was bordered medially by Fo1 and Fo2 and laterally by the lateral OFC (lOFC). A cluster analysis of the cytoarchitectonical features of Fo1-Fo3, subgenual cingulate areas, BA12, lateral and medial areas of the frontopolar cortex, lOFC and areas of Broca's region demonstrated the cytoarchitectonical similarity between the mOFC areas in contrast to all other frontal areas. Probabilistic maps of mOFC areas show a considerable intersubject variability in extent and position in stereotaxic space, and provide spatial templates for anatomical localization of in vivo neuroimaging data via the JuBrain atlas and the Anatomy Toolbox.